IMPROVING GROWTH AND PRODUCTIVITY OF POJ 2878 THROUGH BIPARENTAL CROSSING - Murianingrum M.; Machfud M.; Djumali; Herwati A.; Purwati R.D.; Heliyanto B.; Supriyono; Suhara C. (Russian Journal of Agricultural and Socio-Economic Sciences)
The increase in sugar demand over the last 5 years has led to efforts to increase sugar production, including creating new superior varieties; the biparental crossing is one way to produce new superior varieties. The study was done at IP2TP Karangploso, Malang, Indonesia, from December 2020 to November 2022; it aims to obtain potential clones that produce higher crystals than female parents. Seventeen clones resulting from crosses and one female parent (POJ 2878) were arranged in a Randomized Block Design with 2 repetitions. The results showed that apart from clone 19/18/10, all clones tested produced sugar yield at 5.94-10.88 t/ha, which increased 72.87% from the female parent (4.93 t/ha). Of the clones that experienced an increase, 9 clones (19/3/2, 19/3/4, 19/3/5, 19/3/8, 19/3/11, 19/3/14, 19/ 3/15, 3/19/16, and 3/19/19) showed an increase in sugar yield by 74.83-120.57%, or more than 72.87% of the female parents. The increase in sugar yield occurs through increased sugarcane productivity.